A Review Paper on Big Data with comparative analysis of Hadoop - Priya, (International Journal of Computer Sciences and Engineering, 2019)
Big data is the complete data that is generated by human beings in daily life. Data is gathered from various sources and thus made useful for people by preprocessing it. For processing such huge amount of data (i.e. in terabytes and petabytes), specialized hardware and software is required. Thus, to store, manage, and process the increasing amount of data is really a challenging area of research and development in big data analysis. The objective of this paper is to explore the impact, challenges, architecture of big data and various tools associated with it. This paper also provides a comparative study of Hadoop distributed file system and traditional database and a platform to explore it at various stages.